KOORDINASI SIMPANG AHMAD YANI DAN SIMPANG ADI SUCIPTO DI KABUPATEN MANGGARAI (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2023)
Manggarai Regency is one of the regencies in East Nusa Tenggara Province. The type of road network in Manggarai Regency tends to be linear, but for the center of activity it is in the form of a grid which causes many meetings with intersections with short distances between intersections. Therefore, the intersection becomes the focus of solving transportation problems that are considered so that traffic flows smoothly. In Manggarai Regency, there are two intersections with poor performance with a distance of 250 meters between them, namely the Ahmad Yani Intersection and the Adi Sucipto Intersection. To improve performance at the two intersections, coordination is carried out at the intersection. The calculation method used is MKJI. Before coordinating, looking for the existing performance of the intersection, then optimization is carried out to get the best cycle time. ABSTRAK Kabupaten Manggarai merupakan salah satu kabupaten yang ada di Provinsi Nusa Tenggara Timur. Jenis jaringan jalan di Kabupaten Manggarai cenderung berbentuk linear namun untuk kawasan pusat kegiatan berbentuk grid yang menimbulkan banyak pertemuan dengan simpang dengan jarak antar simpang pendek. Maka dari itu persimpangan menjadi fokus penyelesaian permasalahan transportasi yang diperhatikan agar terjadi kelancaran arus lalu lintas. Di Kabupaten Manggarai terdapat dua simpang yang kinerjanya buruk dengan jarak antar simpang 250 m yaitu Simpang Ahmad Yani dan Simpang Adi Sucipto. Untuk meningkatkan kinerja pada kedua simpang dilakukan pengkoordinasian simpang. Metode perhitungan yang digunakan menggunakan MKJI. Sebelum pengkoordinasian, mencari kinerja eksisting simpang, selanjutnya dilakukan optimasi untuk mendapatkan waktu siklus terbaik.